EFFECT OF DIFFERENCE MECHANICAL FORCE INDUCTION TO OSTEOCLAST AND OSTEOBLAST HEAT SHOCK PROTEIN 25 EXPRESSION: EFEK PERBEDAAN INDUKSI KEKUATAN MEKANIS TERHADAP EKSPRESI HSP25 OSTEOKLAS DAN OSTEOBLAS - Muhammad Nurul Amin (TALENTA, 2012)
The usage of orthodontic appliance is to correct malocclusion involves alveolar bone remodeling. This process isstimulated by mechanical force which obtained from the activation orthodontic appliance. The force was used to depressteeth and the tissues surrounding it. This stress will become a signal to activate heat shock response yielding HSPsynthesis. HSP25 plays a part in osteoclastic bone resorption and osteoblastic new bone forming. The aim of this studywas to explore the change of osteoclast and osteoblast HSP25 expression in the different mechanical force induction atpressure and strain area. The subject was guinea pig (Cavia sp), divided into 2 groups. Control group did not useorthodontic appliance and treatment group was given mechanical force as 90 g, 120 g, and 150 g. Time usage oforthodontic appliance was 5 and 10 days. Osteoclast and osteoblast HSP25 were measured by counting cells after beingconducted by immunohistochemistry method. The result showed that osteoclast HSP25 expression at pressure area on allgroups had increased value compared to strain area and was different statistically. On the other hand, osteoblast HSP25expression at strain area had increased value was compared to at pressure area and especially in group of 120 g and 10days had difference statistically. In conclusion, different mechanical force induction could influence osteoclast andosteoblast HSP25 expression. HSP25 may represent one of the factors that influences osteoclast and osteoblast cellularactivity and coupling process between osteoclast and osteoblast.